2021
DOI: 10.1016/j.sjbs.2021.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum alpha fetoprotein-L3 as an accuracy novel biomarker for the early diagnosis of hepatocellular carcinoma in Egyptian patients

Abstract: Background Most Hepatocellular Carcinomas (HCCs) are diagnosed at an advanced stage. However, HCC early diagnosis is complicated by the coexistence of inflammation and cirrhosis. The unsatisfactory sensitivity and specificity of Alpha-fetoprotien (AFP) for screening of early-stage HCC paved the way for new novel biomarkers to complement AFP such as AFP-L3. The aim of this study was the Evaluation of alpha fetoprotein-L3 (AFP-L3) as earlier marker in diagnosis of hepatocellular carcinoma in Egyptia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In a large multicenter prospective study of hepatitis C virus related HCC, the specificity of AFP-L3 was observed to be 92% but its sensitivity was fairly low at 37%, irrespective of the tumor stage[ 36 ]. On the contrary, a number of recent studies reported a much higher sensitivity of AFP-L3 for diagnosing HCC[ 37 - 39 ]. Ibrahim et al [ 39 ] evaluated the diagnostic efficacy of AFP-L3 among 20 healthy individuals, 40 patients of chronic active hepatitis and 40 HCC patients with underlying chronic hepatitis B (CHB) or C. Among the HCC patients, 30 (75%) had tumor size > 5 cm.…”
Section: How Is Afp Measured?mentioning
confidence: 99%
See 3 more Smart Citations
“…In a large multicenter prospective study of hepatitis C virus related HCC, the specificity of AFP-L3 was observed to be 92% but its sensitivity was fairly low at 37%, irrespective of the tumor stage[ 36 ]. On the contrary, a number of recent studies reported a much higher sensitivity of AFP-L3 for diagnosing HCC[ 37 - 39 ]. Ibrahim et al [ 39 ] evaluated the diagnostic efficacy of AFP-L3 among 20 healthy individuals, 40 patients of chronic active hepatitis and 40 HCC patients with underlying chronic hepatitis B (CHB) or C. Among the HCC patients, 30 (75%) had tumor size > 5 cm.…”
Section: How Is Afp Measured?mentioning
confidence: 99%
“…On the contrary, a number of recent studies reported a much higher sensitivity of AFP-L3 for diagnosing HCC[ 37 - 39 ]. Ibrahim et al [ 39 ] evaluated the diagnostic efficacy of AFP-L3 among 20 healthy individuals, 40 patients of chronic active hepatitis and 40 HCC patients with underlying chronic hepatitis B (CHB) or C. Among the HCC patients, 30 (75%) had tumor size > 5 cm. At a cut-off point of > 12.3 ng/mL, AFP-L3 was 100% accurate in diagnosing the HCC[ 39 ].…”
Section: How Is Afp Measured?mentioning
confidence: 99%
See 2 more Smart Citations
“…Kong et al reported that the combined detection of enhanced CT and contrast-enhanced ultrasound with tumor markers such as AFP is helpful for the early diagnosis of PHC (35237392). Alpha-fetoprotein-L3 (AFP-L3), a subtype of AFP, has been reported to have high specificity for early PHC diagnosis [ 12 , 13 ]. In recent years, Golgi protein 73 (GP73) was found to be significantly elevated in the serum of PHC patients, and it was considered a biomarker for diagnosing early PHC [ 14 , 15 ](33343966).…”
Section: Introductionmentioning
confidence: 99%